Notary Responsibility in Making the Deed of General Meeting of Shareholders of Limited Liability Companies (Analysis of Verdict Number 86/PDT.G/2017/PN.LBP) - Husna Hanifah Kultsum; Mahendra Sanvina Sekti; Fashbir Shabran Jamila; Adam Kurniawan Gazali (Budapest International Research and Critics University, 2022)
This study discusses the responsibilities of a notary in making the deed of the general meeting of shareholders of a limited liability company based on Court Decision Number 86/PDT.G/2017/PN. LBP. Limited Liability Companies are becoming legal entities that are increasingly recognized in the community along with economic developments. In the case of holding a General Meeting of Shareholders of a company, the position of a notary becomes important, especially in terms of making the Minutes of the GMS. The role of the Notary in making the minutes of the GMS meeting can be seen from the public opinion held in each authentic deed, where the notary has the responsibility for the truth of the contents contained in a deed, for what is seen and witnessed in relation to an event concerning a legal act. Thus, the deed made has a proving value as an authentic deed. From this case it can be seen, as a result of the notary's carelessness in making the deed, it can cause harm to interested parties, and result in the deed itself where the notary deed which is an authentic deed which has perfect evidentiary power, but because of a legal defect it can change the position of the deed itself becomes a private deed.